Missing an osteoporotic vertebral fracture - Cheong, A.T.; Khoo, E.M. (Academy of Family Physicians of Malaysia, 2009)
This case illustrates an 80-year-old lady who presented with acute low back pain and finally succumbed from complications of osteoporotic vertebral fracture. Among the contributing factors are delayed diagnosis and a lack of continuity of care. It reminds the practitioners of the importance to look out for red flag symptoms and to have a high index of suspicion for vertebral fracture in high risk patients presenting with low back pain. Â©Academy of Family Physicians of Malaysia.